Quantum computing’s paradigm shift : Implications and Opportunities for Cloud Computing - Brahmam Ainala, Veera; Arikatla, Yaswanth; Seru, Varma; Dasu, Sahil; Bikram, B (Buana Information Technology and Computer Sciences (BIT and CS), 2024)
The field of computing is about to undergo a revolution thanks to quantum computing, a ground-breaking innovation based on the ideas of quantum physics. The enormous implications and potential that quantum computing has for cloud computing are explored in this publication. We examine the difficulties faced by current cryptography systems as well as prospective improvements in fields like machine learning, simulations, and data security as we delve into the basic alterations in computing paradigms. Additionally, we go over the revolutionary possibilities for cloud computing, such as the creation of quantum-safe cloud security solutions, hybrid computing models, and quantum cloud services.